CIRI-CIRI POSYANDU DENGAN CAKUPAN PENIMBANGAN > 70% DI KABUPATEN GOWA DAN KABUPATEN KARAWANG - Iman Sumarno; Herman Sudiman; Sri Prihatini; Vita Kartika; Feri Ahmadi; Dianne Adha; Budi Setiawati; Nur Handayani; Dwi Siska Kumala Putri (Persagi, 2007)
THE CHARACTERISTIC OF SUCCESSFUL POSYANDUS IN GOWA AND KARAWANG DISTRICTS.Background: The need for revitalizing integrated community health services (posyandu) has been emerged since the news on the severe malnourished children in electronic and printed media since 1999, because of public concern. However, all the efforts to revitalize are partial and focused on the provider side. There is no clear method on how should the Posyandu be revitalized. In order to revitalize posyandu it is important to figure out of successful posyandu as a target to be achieved in the revitalization of posyandu. Objectives: To determine the characteristics of Posyandus having coverage of growth monitoring activities more than 70%. Methods: The data used in this article are data of study on revitalizing posyandu in 2006. The study covered 16 Posyandu in the district of Gowa in South Sulawesi and 9 posyandu in the district of Karawang in West Java. The variables were about the leadership in Posyandu, village and Health centre, and health services provided in posyandu. The data were collected by observation. Simple analysis of Chi-square was employed since multivariate analyisis cannot be used in limiting number of cases. Results: It was found that posyandus with coverage there are motor (leader of cadres) that are charismatic, charitable, and friendliness personalities, simple medications, good supplementary feeding, and strong support from informal leaders. This study demonstrated chat high coverage of growth monitoring activities can be achieved even if the motor of posyandus is only simple cadre (charitable and friendly, not charismatic). In this condition the posyandu area with no more than 15 minutes walking distance.Keywords: leaders, medication, supplementary feeding, posyandus